Investigating the Relationship between Professional Self-Concept and the Lifestyle of Nurses in Hospitals Affiliated with Mazandaran University of Medical Sciences - Ali Rahimi; Behzad Hamedani; Nasrin Rasoulzadeh (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk)
Introduction: Nurses have a prominent position in providing healthcare services. There is an undeniable relationship between nurses' professional self-concept and providing care to patients. This study was conducted to investigate the relationship between professional self-concept and the lifestyle of nurses in selected hospitals of Mazandaran cities. Methods: This descriptive study was conducted using a stratified sampling method with a proportional allocation of 200 nurses working in hospitals affiliated with Mazandaran University of Medical Sciences in 2015. Data collection tools included a demographic information form, a nurse professional self-concept questionnaire, and a nurses' lifestyle questionnaire. Data analysis was done with a significance level of P ≤ 0.05. Pearson's correlation coefficient was used to determine the relationship between professional self-concept and nurses' lifestyle. Results: The mean score of nurses' professional self-concept and a lifestyle was 156.55 ± 19.37 and 216.42 ± 5.88, respectively. There was also a significant direct relationship between professional self-concept and nurses' lifestyle. Conclusions: Considering the confirmation of positive correlation between professional self-concept and the lifestyle of nurses, nursing managers can promote healthy lifestyles in nurses by promoting professional self-concept.